Alternative Diagnostic Tool: Multimodality of Policy Implementation - Ricky Putra; Muhammad Ikram; Laurenzt Jenita (Jurnal Global Ilmiah, 2026)
Governance serves as a primary determinant of state legitimacy and public approval, a reality most evident during policy implementation phases and their subsequent socio-economic implications. This research examines the current state of public governance in Indonesia through an innovative diagnostic framework: the technical lens of multimodal transportation logistics. By applying this framework to the complex network of political elites, public managers, citizens, and statutory boundaries, this study identifies a state of chronic bureaucratic congestion plaguing formal institutions. Employing an interdisciplinary research approach to synthesise logistical systems and public administration, the study finds that this congestion primarily stems from the pervasive influence of informal institutions and localised political dynamics. To maintain operational speed and public relevance within this fractured landscape, public managers frequently align institutional conduct with extra-legal, informal channels. Simultaneously, the tendency of political actors to rush large-scale policy implementation without investing in the necessary technical expertise severely exacerbates this systemic friction. This administrative pathology is compounded by a lack of robust professional development for the state apparatus and insufficient capacity-building initiatives for the citizenry. This study concludes that the Indonesian administrative ecosystem is caught in a capability trap characterised by a manufactured inability to execute modern governance, which systematically diminishes institutional performance and ultimately deprives vulnerable citizens of the essential public services to which they are entitled.